nutrition-human-health 2018
DOI: 10.35841/nutrition-human-health.2.1.28-34
|View full text |Cite
|
Sign up to set email alerts
|

Folate and Vitamin B-12 status of anemic pregnant women and association to hemoglobin during antenatal care, 17-37 weeks in Ambo Hospital, Oromia, Ethiopia, a multi regression analysis of socio-economic and serum folate and Vitamin B-12

Abstract: Maternal health during pregnancy has been very critical and important for intergenerational health. According to WHO about half of anemia is believed to be due to iron deficiency anemia. In Ethiopia, the anemia prevalence was reported 22% in pregnant and believed due to IDA. Despite recommendation of iron-folic acid supplementation adherence is still low. The objective of the research was to determine the prevalence of folate and vitamin B-12 deficiency among pregnant and association to anemia during second an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 11 publications
0
24
1
1
Order By: Relevance
“…The prevalence of folate deficiency observed in this study was higher than previous studies reported in Niger at 44.3%, 9 Kenya at 0.8% 8 and Ethiopia at 26.9%. 27 However, it is lower than in Sudan (57.7%) 11 and Senegal (54.3%). 10 In Ethiopia, 46% of women of reproductive age were deficient in folate, 28 which falls within the scope of our study.…”
Section: Discussionmentioning
confidence: 81%
“…The prevalence of folate deficiency observed in this study was higher than previous studies reported in Niger at 44.3%, 9 Kenya at 0.8% 8 and Ethiopia at 26.9%. 27 However, it is lower than in Sudan (57.7%) 11 and Senegal (54.3%). 10 In Ethiopia, 46% of women of reproductive age were deficient in folate, 28 which falls within the scope of our study.…”
Section: Discussionmentioning
confidence: 81%
“…Among the studies, nine [ 4 , 10 , 27 – 32 , 52 ] were cross-sectional studies, and one was a case-control [ 51 ]. Regarding the study setting, six of the studies [ 4 , 27 , 28 , 30 , 31 , 52 ] were done at the community level, while the other four [ 10 , 29 , 32 , 51 ] were institutional-based. Three studies [ 4 , 28 , 30 ] were conducted at a national level, whereas the other seven were conducted at the sub-national/local level—three in Oromia Region [ 29 , 32 , 52 ], one in Amhara Region [ 31 ], one in Sidama Region [ 27 ], and two in Addis Ababa City Administration [ 10 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [ 10 , 27 , 29 , 32 , 51 , 52 ] were conducted among pregnant women, and two were [ 28 , 30 ] done among non-pregnant/non-lactating women. However, two studies [ 4 , 31 ] were performed generally in WRA without specifying the physiological status of the women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Kebiasaan ibu hamil mengkonsumsi makanan dan minuman yang beragam, seperti contoh minum teh dan kopi juga mempengaruhi status gizi khususnya kadar Hb ibu tersebut. [7] Selama hamil kebutuhan gizi meningkat dibandingkan dengan kebutuhan sebelum hamil. Pada trimester II kehamilan terjadi penurunan konsentrasi Hb yang mencapai titik terendah dan akan meningkat kembali pada trimester ke III.…”
Section: Pendahuluanunclassified